Subsaharian African Cities in the French Geography and in the Documentary Production : a Geography of “Ghost Cities” ? - (:unkn) unknown (My University, 2011)
During the XXth Century, African Subsaharian cities have long been neglected by the French Geography for various reasons. The paper’s object is devoted to analyse this situation, more specifically as far as Malagasy studies are concerned. When African cities have been studied by geographers, it was often according to rural or backward-looking points of view which delivered an exotic and altered image of them. This stereotyped vision of urban Africa is also present in documentary productions intented to a wider audience. In school geography, in which the study of Africa is generally on the decline, urban Africa still has a place in the programs but the main focus is devoted to poverty and informal economy. Nonetheless, since the seventies, most of the scientific geography has left apart these old prejudices and has extended the studied themes. Ever since, French urban geography about Africa has been catching up with the other social sciences and now deals with a very large field. Though, some themes such as modernity or social elites remain understudied, whereas some papers still convey urbaphobic ideas.
Keywords: African Research